Equilibrios epistémicos frente a la crisis ambiental: un estudio a partir del Caso del Atún Rojo del Sur del Tribunal del Mar en la antesala de sus cuarenta años de creación - Villarreal, Julio Francisco (2022)
This paper attempts to demonstrate that the solution rendered by the International Tribunal for the Law of the Sea in the Southern Bluefin Tuna Case, although epistemically superior to the one that would have involved only considering the experts advising of each of the opposing parties dicta, would, in any case, prove to be sub-optimal. Indeed, such a forum, despite the provisions to that effect of the United Nations Convention on the Law of the Sea 289 article, would refrain from consulting and discussing with the experts the merits of the question submitted to its consideration. As a direct implication of such decision, the International Tribunal for the Law of the Sea could not have contributed to the knowledge, by the opposing parties, of the merits of their claims in a transcendental manner to the terms in which those parties raised, initially, their own claims. As a straight consequence of such a decision, the International Tribunal for the Law of the Sea deprived itself of any possibility of providing a truly consistent contribution to such dispute resolution, regardless of the following Arbitral Tribunal’s decision merits. In this sense, this paper attempts to prove the strict causal relationship between failing to consider the otherness dictum and making epistemically deficient decisions by means of the International Tribunal for the Law of the Sea ruling in the Southern Bluefin Tuna Case.